Fatigue self-management strategies in cancer survivors: a systematic literature review - Peixoto, Tiago André dos Santos Martins (2021)
Context: In addition to having a significant impact on cancer survivors’ quality of life, fatigue is a condition that influences self-management and health-disease transition. Objectives: This study aims to identify fatigue management strategies used by cancer survivors at the end of treatment through a literature review. Review method: Systematic literature review based on the Joanna Briggs Institute model. Of the 815 articles found, 8 were included. Interpretation of results: Strategies related to physical exercise, energy conservation, cancer-related symptom management, self-efficacy perception, coping style, social networks and social support can contribute effectively to reduce and manage fatigue levels, and promote the management of the disease that triggers the adaptation to this new condition. Conclusion: Strategies related to physical exercise, disease-related symptom management, perceived self-efficacy, coping styles and social support are effective for self-managing fatigue in the survival phase.